DIVERSITY AND DISTRIBUTION OF ESSENTIAL OIL–BEARING PLANTS IN CENTRAL ASIA (International Conference on Economics, Finance, Banking and Management, 2025)
The study presents a comprehensive overview of the diversity, taxonomic composition, and geographical distribution of essential oil–bearing plants across Central Asia, with a particular focus on the flora of Uzbekistan. A total of 42 species belonging to 29 genera and 8 families were identified within the Bukhara region, accounting for 6.5% of its total vascular flora. The findings highlight the dominance of Apiaceae, Lamiaceae, and Asteraceae, and demonstrate significant floristic similarities between the Bukhara and Navoi regions. The results contribute to understanding the distributional patterns of aromatic plants in arid environments and provide a foundation for further phytochemical and ecological research.